2017
DOI: 10.3390/app7020166
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Succession and the Dynamics of Chemical Compounds during the Solid-State Fermentation of Pu-erh Tea

Abstract: An in-depth knowledge of the microbiota and metabolites in the solid-state fermentation (SSF) of Post-fermented Pu-erh tea (Pu-erh Shucha, PFPT), a Chinese traditional tea with various health benefits, is essential to develop modern fermentation technology. In this work, the microbial diversity and succession in two laboratory-developed SSF protocols for PFPT were investigated using pyrosequencing analyses of the bacterial 16S rRNA and fungal 18S rRNA genes. The active bacteria in the initial stages of SSF (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Aspergillus oryzae is one of the most important micro-organisms involved in the fermentation of soy sauce, and the autolysate may promote the flavour compounds such as alcohols, aldehydes, phenols and esters . Aspergillus was also predominant in vinegar Pei during acetic acid fermentation (Liu et al 2004; Wang et al 2016) and Pu-erh tea during postfermentation (Ma et al 2017b). This phenomenon was also consistent with previously published data in tofu substrate that Aspergillus, Pichia, Saccharomyces and Bacillus were dominant throughout the fermentation process, in which Aspergillus and Bacillus could produce potential proteolytic and amylolytic enzymes (Suntinanalert et al 2005).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Aspergillus oryzae is one of the most important micro-organisms involved in the fermentation of soy sauce, and the autolysate may promote the flavour compounds such as alcohols, aldehydes, phenols and esters . Aspergillus was also predominant in vinegar Pei during acetic acid fermentation (Liu et al 2004; Wang et al 2016) and Pu-erh tea during postfermentation (Ma et al 2017b). This phenomenon was also consistent with previously published data in tofu substrate that Aspergillus, Pichia, Saccharomyces and Bacillus were dominant throughout the fermentation process, in which Aspergillus and Bacillus could produce potential proteolytic and amylolytic enzymes (Suntinanalert et al 2005).…”
Section: Discussionsupporting
confidence: 87%
“…) and Pu‐erh tea during postfermentation (Ma et al . ). This phenomenon was also consistent with previously published data in tofu substrate that Aspergillus , Pichia , Saccharomyces and Bacillus were dominant throughout the fermentation process, in which Aspergillus and Bacillus could produce potential proteolytic and amylolytic enzymes (Suntinanalert et al .…”
Section: Discussionmentioning
confidence: 97%
“…Nineteen species of Pseudomonas were identified from this genus in total (Table S2), with most identified as non‐infectious species, except for Pseudomonas oryzihabitans that was detected in sample W2, in a proportion of 0.03%. This genus has previously been shown to be dominant in Korean kimchi, ‘Jiaozi’, brined table olive, Pu‐erh tea, and ‘doubanjiang‐meju’, which is an anaerobic fermentation food derived from broad beans. Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…As a well-known traditional Chinese fermented food with multiple health benefits, such as hypolipidemic, antimutagenic, antioxidative, antitumor, antiobesity, and toxicity-suppressing activities (16), it is popular in Southeast Asia and is becoming increasingly popular in the Western world. Microbial communities in the fermentation of pu-erh tea have previously been studied using culture methods and culture-independent approaches, including denaturing gradient gel electrophoresis, 16S rRNA gene clonal library, and next-generation sequencing (17). Recently, a study by Li et al (18) using shotgun metagenomic and metabolomic analyses showed that significant variations in the composition of microbiota, collective functional genes, and flavor compounds occurred during the fermentation process.…”
Section: Introductionmentioning
confidence: 99%